Constructivist theories of ethnic politics - Chandra, Kanchan, 1971- (New York : Oxford University Press, 2012)
Taking the possibility of change in ethnic identity into account, this book shows and dismantles the theoretical logics linking ethnic diversity to negative outcomes and processes such as democratic destabilisation, clientelism, riots and state collapse. Even more importantly, it changes the questions we can ask about the relationship between ethnicity, politics and economics.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Ethnicity -- Political aspects; Ethnic relations -- Political aspects; Ethnic groups -- Political activity; Identity politics; Ethnicity -- Philosophy